PENERAPAN BOOKLET UNTUK PENINGKATAN PENGETAHUAN DAN KEPATUHAN MINUM ANTIRETROVIRAL PADA ORANG DENGAN HIV/AIDS - Vitrilina Hutabarat; Stefani Anastasia Sitepu (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Antiretroviral therapy is a specific on people with HIV/AIDS. One of which was to increase the knowledge and adherence in taking the drugs through health education. The use of booklet in this effort showed an effective result in increasing the knowledge and obedience in treatment beside increasing the quality of life. The purpose of the study was to evaluate the influence of health education using booklet on the increase of knowledge and adherence.This was a quasi alphabet experiment study with pre posttest with control two group design. The study was conducted during May until July 2020 at Adam Malik Hospital, Medan. The samples were 60 patients. Data analysis using Wilcoxon and Mann-Whitney test. Questionnaires is the instrument of this study. The result showed in the intervension group knowledge pre post increased by 5.6% while the 2,9% in the control group (p=0,003), and for adherence to the intervention group rise 53.3% whereas in the control group 3,3% (p=0.000).Count relative risk the knowledge gained for RR(95% CI):3,33 (1,02-10,92) and count relative risk adherence for compliance RR(95% CI): 2,07 (1,40-3,05).Age,gender,education and social support showed insignificant differences.The conclusion of this study revealed that health education using booklet influenced the increase of knowledge and adherence.